2004
DOI: 10.1159/000076710
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar Thermocoagulation in the Management of Acardiac Twins

Abstract: Objective: To demonstrate the equipment setup and the application of monopolar thermocoagulation in the management of acardiac twins. Methods: We described 2 cases of acardiac acephalus twins who developed congestive heart failure and polyhydramnios at 20 weeks of gestation. A monopolar wire electrode was inserted through a 14-gauge trocar under ultrasound guidance. The inter-twin circulation was interrupted and confirmed by color Doppler flow examination. Results: Case 1 was detected at 20 weeks of gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the past 3 decades, several methods for intrauterine intervention have been developed, aiming to improve the outcome for the pump twin [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75]. Most studies in the literature have reported treatment in 1-10 cases, with only a handful examining larger series.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 3 decades, several methods for intrauterine intervention have been developed, aiming to improve the outcome for the pump twin [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75]. Most studies in the literature have reported treatment in 1-10 cases, with only a handful examining larger series.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment methods for TRAP sequence, such as cord occlusion [17][18][19][20] , anastomotic vessel ablation 21,22 and intra-acardiac fetal ablation techniques, have been reported 23,24 . RFA provides good results owing to its relatively low invasiveness and ease of treatment 20,[25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a perfusion electrode, known as a ''cooled-tip'' needle, has been developed and serves as a more powerful tool for creating larger volumes of necrosis in less time than the old monopolar technique [23,24]. The continuous cooling of the needle tip via circulation of chilled saline allows for greater transmission of microwave energy into the tissues and permits heating and necrosis far from the electrode without tissue charring [25].…”
Section: Discussionmentioning
confidence: 99%